Plankton Community Changes From Warm to Cold Winters in the Oligotrophic Subtropical Ocean - Armengol, Laia; Franchy, Gara; Ojeda, Alicia; Hernández-León, Santiago (Frontiers in Marine Science, 2020)
Subtropical gyres are large areas of the ocean characterized by high stratification, low nutrients, and low primary production. The Canary Current System (CanCS) shows a rather strong seasonal thermocline during most of the annual cycle, which erodes from January to March promoting the so-called Late Winter Bloom (LWB). Atmospheric deposition from the Sahara desert is also another key feature of the CanCS providing additional nutrients to the euphotic zone. As a consequence of global warming, these oligotrophic regimes systems are expanding and the temperature increase affects phytoplankton, and reverberate on the food web structure and biogeochemical cycles. In this sense, the effect of warming and dust deposition on the planktonic community remains poorly know in the CanCS. Here, we show the effects of a 0.5ºC increase in ocean temperature during two consecutive years. During 2011, winter temperature allowed the development of the LWB, promoting the increase of autotrophic cells and the coexistence of the microbial loop and the “classic” trophic web. The former predominated before and after the LWB, while the latter prevailed during the LWB. The high temperature during 2010 prevented the LWB development, causing highly oligotrophic conditions and Saharan dust being the only nutrient input into the environment. During this warm year, we found a dominance of small cells such as nanoflagellates and dinoflagellates, and surprisingly high biomass of mesozooplankton, hinting at the “tunneling effect” as an alternative trophic pathway. These changes show the impact of a slight increase in temperature in this oligotrophic system and how future scenarios in the context of global warming could promote considerable shifts in the trophic web structure.